The status of evidence obtained unlawfully: a comparative appraisal of the laws in some selected Common law jurisdictions and Islamic law perspective - Shair Mohamed, Mohd Akram; Mohamad Yunus, Mohamad Ismail (Serials Publications, 2016)
Evidence may be obtained illegally, for example by a crime, tort or a breach of contract or in breach of statutory or other provisions governing the powers and duties of the police or others involved in investigating crime. Evidence may also be obtained improperly or unfairly for example by trickery, deception, bribes, threats or inducements. At one extreme, the view could be taken that evidence, which is relevant and otherwise admissible, should not be excluded because the means by which it was obtained: whether illegal, improper or unfair, to exclude it, would in some cases, result in injustice including the acquittal of the guilty. On this view, all evidence, which is necessary to enable justice to be done would be admitted, and those responsible for the illegality or impropriety could be prosecuted, sued or disciplined. The view at the other extreme would be that illegally or improperly obtained evidence should always be excluded; to admit it, might encourage the obtaining of evidence by such means. On this view, all such evidence would be excluded, even if this would sometimes result in injustice including the guilty going free, in order that those responsible for the illegality or impropriety are in future compelled to respect and are deterred from invading the civil liberties of the citizens. The modern law of evidence in Australia, Canada, Great Britain, Ireland, Malaysia, Scotland and Singapore represents a compromise between these two extremes. So, although generally it reflects in relation to admissibility as a matter of law, it also empowers the trial judge to exclude as a matter of discretion. As to the discretion to exclude the Australian, Canadian, Irish, Scottish and latterly, the English courts have adopted a wider aspect of the discretion, while Malaysia has taken the narrower aspect, the Singaporean courts have further restricted the exclusionary discretion.